The Western Washington State College Clinical Program for Teacher Education at Seattle, Washington - Western Washington Univ., Bellingham; Western Washington Univ., Bellingham ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
This program is the 1972 Distinguished Achievement Award Entry from Western Washington State College. This performance-based, field-centered program is located in six Seattle schools (K-12) which are ethnically, socially, and economically mixed. The participants complete the program in 2 quarters and on graduation are issued a provisional certificate to teach. To help define his future teaching role, each participant a) studies a variety of teaching styles in various classroom situations and b) assesses his own personal teaching style and practices. In developing his own style, the participant selects individually paced, performance-based instructional modules. He is assisted by a clinical professor and supervising teacher. This training design allows each candidate to develop a teaching style which is compatible with his personality. The attainment of the pupil's goals is the participants' criterion of success. The self-supporting program exists in a parity relationship with college, school district, and professional education association personnel. (The appendixes include information on program objectives, practica, evaluation, and the functions of learning.) (Author/BRB)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Behavioral Objectives; Clinical Experience; Competency Based Teacher Education; Cooperative Planning; Field Experience Programs; Inservice Education; Student Behavior; Teaching Styles; Distinguished Achievement Awards Entry